Evaluation of the attack rates and level of damages by the fall armyworm, Spodoptera frugiperda (Lepidoptera: Noctuidae), affecting corn-crops in the northeast of Argentina - Ayala, Oscar R.; Navarro, Fernando; Virla, Eduardo G. (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2022)
The fall armyworm (FAW) is the most important threat to corn crops in Argentina, and there exists very little up-to-date information on its actual pest status because the available literature was published more than 20 years ago. Therefore, field surveys were carried out in the northeast of Argentina, in order to establish the attack rates and injury levels of the pest in relation to the crop phenology. The study was carried out at two localities: Colonia Benítez, an agricultural region, and Tapenagá, a cattle-raising area. At each site two 1-ha plots were sown either with a Bt-corn expressing Cry 1F protein or with an untransformed corn germplasm. Optimal and late sowing was assayed and FAW larval abundance, relative age composition, attack rates and level of damage to corn were recorded. At the moment of the field experiments, Bt-corn was not affected by FAW larvae. However, untransformed germplasms were severely affected by FAW larvae, with an average of attacked plants of 18% or more. In contrast to data obtained 30 years ago, higher values of FAW density were registered. Levels of damage to corn plants were higher after the V4 stage. It was found that the sowing date affected the infestation levels and early seeding avoided high armyworm densities that develop later in the season; in northern Argentina, this was only relevant in agricultural areas.